Characteristics and mineralogy of sediments in the Hongsa lignite deposit, northwestern Laos - Sattraburut, Thunyapat; Thasod, Yupa; Ratanasthien, Benjavun; Vongvassana, Sirasit (Geologos, 2024)
Two sediment cores from the central part of the Hongsa lignite deposit in northwestern Lao PDR (Lao People’s Democratic Republic; Laos) have been analysed in order to understand their sedimentary characteristics using grain-size analysis, petrography, X-ray diffraction and scanning electron microscopy. This analysis has revealed that the deposit is primarily composed of fine-grained sediments, mainly silt and clay, with quartz as the dominant mineral and trace amounts of other minerals such as kaolinite, illite and montmorillonite. Gypsum and chlorite have also been found in some layers. Scanning electron microscope analysis has revealed a card-house structure of clay minerals, suggesting sedimentation from suspension driven by physico-chemical reactions influenced by pH and water chemistry. This arrangement increases porosity and water retention, significantly affecting the permeability and mechanical properties of sediments. Petrographic analysis has documented angular quartz and poorly sorted sediments, indicating minimal sediment reworking or short-distance sources. The palaeoenvironment of the Hongsa Basin, reconstructed from various rock units, suggests low-energy water conditions for the Underburden and moderate sediment supply in a wet forest swamp or bush moor environment for the Lower Lignite Zone Formation. The Middle Lignite Zone Formation indicates a more limited sediment supply in a similar environment, while Interburden Formation 1 suggests overbank deposits or stagnant water deposits. In summary, the Neogene Hongsa lignite deposit is characterised by fine-grained sediments, indicating low-energy water currents in mire environments. Occasional flood events brought coarser grains, although movement of facies should also be taken into account. The mineral composition suggests the presence of components derived from recycled sedimentary rocks along the northern border of the Hongsa Basin.